2006
DOI: 10.1007/s11136-005-0381-x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Depression: Predictive Models

Abstract: The purpose of this study was to examine the predictive factors of quality of life for inpatients with depressive disorders. Eighty-three patients (mean age 44; 73% female) with depressive disorders were recruited from the psychosomatic ward of a medical center in the northern part of Taiwan. The predictive models of this study were established by encompassing three constructs: clinical variables, demographics, and perceived competence. The outcome variables of this study included an overall quality of life sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 45 publications
0
19
0
7
Order By: Relevance
“…Though several studies [36,[44][45][46][47][48][49][50] have shown that low scores in depression as measured by the BDI in healthy participants are valid assessments of depressive symptoms, which can be interpreted meaningful Figure 1. Scatter plots depicting the distribution between heartbeat perception and depression as well as between heartbeat perception and anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though several studies [36,[44][45][46][47][48][49][50] have shown that low scores in depression as measured by the BDI in healthy participants are valid assessments of depressive symptoms, which can be interpreted meaningful Figure 1. Scatter plots depicting the distribution between heartbeat perception and depression as well as between heartbeat perception and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…[43] The inventory has been shown to be valid and reliable for both subjects with and without depressive disorders. [36,[44][45][46][47][48][49][50] Trait anxiety and depression scores were used for correlation and regression analyses between these variables and interoceptive awareness.…”
Section: Questionnaire Datamentioning
confidence: 99%
“…The inventory has been shown to be valid and reliable for both subjects with and without depressive disorders (e.g. [59]). …”
Section: Questionnaire Datamentioning
confidence: 99%
“…Assuming that upbringing determines coping strategies utilized by the subject facing stressful situations, which in turn impact onto quality of life, we conjectured that parental care could be associated with adult quality of life through the kind of coping strategies used. Current depressive symptoms and recent life events are included in this hypothesis as mediator variables [19,20].…”
Section: Introductionmentioning
confidence: 99%